2021
DOI: 10.1002/adfm.202107826
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscience versus Viruses: The SARS‐CoV‐2 Case

Abstract: The outbreak of the coronavirus (SARS‐CoV‐2) pandemic, its rapid spread, and its fatal consequences clearly showed mankind the overwhelming power of nature, and the importance of interdisciplinary research to counter it. Herein, it will be pointed out what challenges arise in fighting nanosized viruses, which feature an outstanding ability to alter their structure and properties to adapt to infection processes, and why nanoscience is extremely powerful to address them. To learn from the past and to be best pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 459 publications
(609 reference statements)
0
9
0
Order By: Relevance
“…Nanoparticles can be used to combat SARS-CoV-2 by targeting mechanisms that affect the viral entry inside the host until they get activated. By blocking the surface proteins on the virus, the virus gets inactivated, so nanoparticles are designed specifically for virus-expressed proteins and could diminish viral internalization (Goscianska et al, 2022). Metal nanoparticles can block the virus's attachment to the host cell, thereby inhibiting the internalization of the virus and impairing the replication of the virus during viral entry.…”
Section: Nanomedicine's Role In Covid-19 Treatmentmentioning
confidence: 99%
“…Nanoparticles can be used to combat SARS-CoV-2 by targeting mechanisms that affect the viral entry inside the host until they get activated. By blocking the surface proteins on the virus, the virus gets inactivated, so nanoparticles are designed specifically for virus-expressed proteins and could diminish viral internalization (Goscianska et al, 2022). Metal nanoparticles can block the virus's attachment to the host cell, thereby inhibiting the internalization of the virus and impairing the replication of the virus during viral entry.…”
Section: Nanomedicine's Role In Covid-19 Treatmentmentioning
confidence: 99%
“…Additionally, the work analyzes the efficiency of ZIF-8-based coating against dangerous microbial pathogens and SARS-CoV-2’s surrogates which provides fresh insights into the field and to already successfully developed solutions [47] , [48] , [49] . The research contributes to the global response to addressing COVID-19 by examining a potentially effective solution for reusable protective materials capable of deactivating SARS-CoV-2 virus and other respiratory viruses [50] , [51] , [52] .…”
Section: Introductionmentioning
confidence: 99%
“…Spike proteins on the surface of the coronaviruses can recognize some cell receptors and facilitate virion entry into the host cells . Nasal sprays that can either inactivate the viruses or block its entry into cells are the potent alternatives for preventing the viral spread to the lung or the surrounding people. These attempts include nanobodies, nanodecoys, , nanoenzymes, and antiseptics. Previous publications have demonstrated that inhalation of angiotensin converting enzyme II (ACE2) nanodecoys derived from human lung spheroid cells (LSCs) can bind and neutralize SARS-CoV-2, protect the host lung cells from infection, and accelerate clearance of SARS-CoV-2 mimics from the lungs . The nanodecoys were found to reside in the lungs for over 72 h post-delivery.…”
Section: Introductionmentioning
confidence: 99%